USING OF THE COVER AMOUNTS METHOD FOR OPTIMIZATION OF INCOME - A. V. Volkov; V. E. Sidorchuk (Литьë и металлургия, 2007)
The method of cover amounts (marginal income) gives possibility to determine profitableness of each kind of the production and their real contribution into the result of work of enterprise.